2012
DOI: 10.1111/j.1472-765x.2012.03220.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and molecular identification of human adenoviruses and enteroviruses in wastewater from Morocco

Abstract: Aims:  Reclaimed wastewater is a considerable water resource in Morocco. Its agricultural reuse requires an assessment of viral contamination. The aim of this study was to detect both infectious and noninfectious human adenoviruses (HAdV) and enteroviruses (EV) in raw wastewater and treat effluent from wastewater treatment plants (WWTPs) and domestic sewage in Morocco. Methods and Results:  A total of 22 samples were analysed. A polyethylene glycol (PEG) precipitation method was used, followed by integrated ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 33 publications
2
10
0
1
Order By: Relevance
“…The results correlate with those obtained in our previous study, in which we have detected more HAdV than HEV using the PEG precipitation method (26) . The same results were obtained by Kokkinos et al, 2010 (4) when the ultracentrifugation method was used, with 40% (10/25) rate of EV and HAdV, and 4% (1/25) of HAV.…”
Section: Assessment Of the Viral Genome By Pcrsupporting
confidence: 82%
See 2 more Smart Citations
“…The results correlate with those obtained in our previous study, in which we have detected more HAdV than HEV using the PEG precipitation method (26) . The same results were obtained by Kokkinos et al, 2010 (4) when the ultracentrifugation method was used, with 40% (10/25) rate of EV and HAdV, and 4% (1/25) of HAV.…”
Section: Assessment Of the Viral Genome By Pcrsupporting
confidence: 82%
“…In previous study (26) , we have seen a decrease in infectious viruses in treated effluent for EV and HAdV in 11.5% (1/9) and 22.5% (2/9), respectively. Otherwise, Hewitt et al, 2011 (43) reported that the rate of positive treated effluents samples from activated sludge WWTP has decreased to half for HAdV and quarterback for EV.…”
Section: Presence Of Infectious Ev and Hadv In Raw Wastewater And Trementioning
confidence: 99%
See 1 more Smart Citation
“…Environmental surveillance is a highly sensitive method for detecting enteroviruses such as PVs in environmental samples, and this practice has been adopted by many countries and regions worldwide (13)(14)(15)(16)(17)(18)(19). It is critically important to routinely monitor sentinel sites for the emergence of novel VDPV strains and the importation of wild PV from countries where the disease is endemic.…”
mentioning
confidence: 99%
“…Integrated cell culture and PCR (i.e., ICC-PCR) developed in the late 1980s still provides a reliable method for practical analysis and direct monitoring of environmental samples for EVs and other viral pathogens recovered from environmental samples (Amdiouni et al, 2012;Chapron et al, 2000;Choo and Kim, 2006;Lee et al, 2005;Reynolds, 2004;Reynolds et al, 1996). More recently, these techniques have been used in combination with viral metagenomics approaches for cell culture evaluation of the virologically quality of wastewater (Aw et al, 2014).…”
Section: Detection Methodsmentioning
confidence: 99%